2020
DOI: 10.3390/nu12041152
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Nutritional Energy and Macronutrient Intake with Pregnancy Outcomes in Czech Pregnant Women

Abstract: Maternal nutrition and metabolism play important roles for the well-being of both mother and fetus during pregnancy. This longitudinal study brings an original evaluation of the relationship between the nutritional energy and macronutrients intake (NEMI) and pregnancy outcomes and an assessment of the changes in such intake over the previous ten years. Sixty-five healthy Czech pregnant women were examined in three pregnancy periods (1st: 17th–27th; 2nd: 28th–35th; 3rd: 36th–38th gestational weeks). Results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Low overall energy and protein intake at 16 weeks' gestation were also associated with increased gestation at delivery, suggesting that gestation is increased in women with lower overall food intake. Previous research in a small cohort found similar results with both carbohydrate intake (g/d per patient weight in kilograms) and overall energy intake between 17 and 27 weeks' gestation being significantly inversely associated with gestation of delivery (carbohydrate: r = −0.131, p < 0.05, energy intake: r = −0.133, p < 0.05) [15]. Neither fat nor protein intake in this gestational time period were associated with gestation at delivery.…”
Section: Discussionsupporting
confidence: 70%
“…Low overall energy and protein intake at 16 weeks' gestation were also associated with increased gestation at delivery, suggesting that gestation is increased in women with lower overall food intake. Previous research in a small cohort found similar results with both carbohydrate intake (g/d per patient weight in kilograms) and overall energy intake between 17 and 27 weeks' gestation being significantly inversely associated with gestation of delivery (carbohydrate: r = −0.131, p < 0.05, energy intake: r = −0.133, p < 0.05) [15]. Neither fat nor protein intake in this gestational time period were associated with gestation at delivery.…”
Section: Discussionsupporting
confidence: 70%
“…Pregnant women with low protein intake are at risk of LBW 6 (54.5%) while those with adequate protein intake may experience LBW 3 (4.3%). The results of this study were proven by Najpaverova et al (2020) who explained that protein intake during pregnancy provides benefi ts for fetal growth and development. Protein intake is very helpful in the process of fetal growth during pregnancy.…”
Section: Resultsmentioning
confidence: 58%
“…A large body of epidemiological studies has indicated a positive association between maternal protein intake and neonatal anthropometric characteristics [ 7 , 8 , 9 , 10 , 11 , 12 ]. However, there is significant evidence that protein may exhibit an inverse [ 13 , 14 ] or U-shaped relationship with fetal growth [ 15 , 16 ], suggesting that we are still far from identifying the ideal protein intake for optimal birth size outcomes [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%